A comparison study between collinearity condition, coplanarity condition, and direct linear transformation (DLT) method for camera exterior orientation parameters determination - El-Ashmawy, Khalid L. A. (Geodesy and Cartography, 2015)
The present work emphasizes on using collinearity condition, coplanarity condition and DLT method for determining the camera exterior orientation parameters. The derivation of the mathematical formulation based on each suggested methods is explained. The comparison of the results of the methods was performed based on accuracy aspects using mathematical and actual photogrammetric data. The used data shows that the suggested methods are suitable for camera exterior orientation parameters determination for a block of photographs of any size. The results of this investigation prove that the accuracy of using coplanarity equations is slightly better than using collinearity equations or DLT method. Although the results of the DLT method are less accurate than those of using collinearity or coplanarity equation, DLT method is essential when the necessary information for the collinearity or coplanarity model is not available. This paper shows the necessity for the mathematical photogrammetric data for testing the photogrammetric studies.